Influence of Pore Water Chemistry on Hydraulic Conductivity of Kaolinite Suspensions. (2016) - Vitale, Enza; Cecconi, Manuela; Croce, Paolo; Deneele, Dimitri; Pane, Vincenzo; Russo, Giacomo; Vecchietti, Alessia
Abstract: The role of pore water chemistry on particle aggregation and soil formation during sedimentation process has been investigated for a kaolinite clay suspensions. The modification of surfaces charge properties of clay minerals induced by different pore water chemistry rules the particles arrangement. As a consequence, at volume scale the sedimentation behaviour and in turn the physical, mechanical and hydraulic behaviour of the formed soil skeleton are changed. Sedimentation tests on several suspensions showed the influence of different aggregation on settling and self-weight consolidation stages. Hydraulic conductivity of kaolin suspensions has been estimated from the settling velocity recorded in sedimentation tests. Test results showed the relevant dependency of the hydraulic conductivity of the clay suspensions on the particle arrangement induced by the pore water chemistry.